Exposure effects of endotoxin-free titanium-based wear particles to human osteoblasts - Costa, Bruna C. [UNESP]; Alves, Alexandra C.; Toptan, Fatih; Pinto, Ana M.; Grenho, Liliana; Fernandes, Maria H.; Petrovykh, Dmitri Y.; Rocha, Luís A. [UNESP]; Lisboa-Filho, Paulo N. [UNESP] (Elsevier, 2019)
Titanium-based materials are widely employed by the biomedical industry in orthopedic and dental implants. However, when placed into the human body, these materials are highly susceptible to degradation processes, such as corrosion, wear, and tribocorrosion. As a consequence, metallic ions or particles (debris) may be released, and although several studies have been conducted in recent years to better understand the effects of their exposure to living cells, a consensual opinion has not yet been obtained. In this work, we produced metallic-based wear particles by tribological tests carried out on Ti-6Al-4V and Ti-15Zr-15Mo alloys. They were posteriorly physicochemically characterized according to their crystal structure, size, morphology, and chemical composition and compared to Ti-6Al-4V commercially available particles. Finally, adsorbed endotoxins were removed (by applying a specific thermal treatment) and endotoxin-free particles were used in cell experiments to evaluate effects of their exposure to human osteoblasts (MG-63 and HOb), namely cell viability/metabolism, proinflammatory cytokine production (IL-6 and PGE2), and susceptibility to internalization processes. Our results indicate that tribologically-obtained wear particles exhibit fundamental differences in terms of size (smaller) and morphology (irregular shapes and rough surfaces) when compared to the commercial ones. Consequently, both Ti-6Al-4V and Ti-15Zr-15Mo particles were able to induce more pronounced effects on cell viability (decrease) and cytokine production (increase) than did Ti-6Al-4V commercial particles. Furthermore, both types of wear particles penetrated osteoblast membranes and were internalized by the cells. Influences on cytokine production by endotoxins were also demonstrated.
Keywords: Biological effects; Degradation; Endotoxins; Titanium implants; Wear particles